La inversión en investigación científica, desarrollo tecnológico e innovación tecnológica y su incidencia del beneficio tributario en la empresa constructora Coliseo Trujillo S.A., año 2016 - Gonzáles García, Nataly Fiorela (2017)
The present research work has the purpose to make known to the government as agents of a new enterprise culture gives enterprises a tax benefit of deduct up to 175% of the expenditure incurred in investing in scientific research, technological development and technological innovation achieving this way to reorient the business through this incentive. Therefore, the present study is aimed at analyzing whether the tax benefit of investment in scientific research, technological development and technological innovation is positively affected by the construction company “Coliseum Trujillo” S.A. for the period 2016. According to the investigations carried out in the construction company “Coliseum Trujillo S.A.” through the application of interviews applied to administrative staff Financial it was determined that the company is aware of the incidence of taxation to invest in scientific research, technological development and technological innovation and would be interested in eligible for this benefit. Through the development of this research work we want to show that investing in scientific research, technological development and technological innovation far from incurring expenses to the construction company “Coliseum Trujillo S.A.” for the period 2016 it is beneficial in terms of the expense deductible reducing the taxable base to determine the income tax of the year 2016 tax positively affecting the time that the construction company “Coliseum Trujillo S. A.” Improves The competitiveness of their organization and thus promotes the economic growth of the country.